1992
DOI: 10.1055/s-0038-1656335
|View full text |Cite
|
Sign up to set email alerts
|

High Level Expression of Active Human Prothrombin in a Vaccina Virus Expression System

Abstract: SummaryWe have worked out an efficient and time saving procedure for the expression of recombinant human prothrombin. The glycoprotein was expressed in the vaccinia virus expression system in several mammalian cell lines. The kidney cell lines Vero and BHK and the human cell line Hela were found to efficiently secrete prothrombin. Expression levels of 3–4 µg of factor II per 106 cells per day corresponding to 18–23 mU per 106 cells per day were achieved. Since the expression levels obtained with the vaccinia v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…A similar observation was reported by Arp et al, (5) who found that an increase in MOI from 2 to 10 did not significantly increase the yield of HTLV-1 gp46. Falkner et al (16) expressed prothrombin and Factor II in Vero, BHK, and HeLa cells by infection with a single recombinant vaccinia virus, and obtained yields for Factor II and prothrombin of 3-4 µg/ 10 6 cells and 1-4 µg/10 6 cells, respectively. They also determined the MOI effect in plates and found similar yields when MOI 0.1-10 were used.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was reported by Arp et al, (5) who found that an increase in MOI from 2 to 10 did not significantly increase the yield of HTLV-1 gp46. Falkner et al (16) expressed prothrombin and Factor II in Vero, BHK, and HeLa cells by infection with a single recombinant vaccinia virus, and obtained yields for Factor II and prothrombin of 3-4 µg/ 10 6 cells and 1-4 µg/10 6 cells, respectively. They also determined the MOI effect in plates and found similar yields when MOI 0.1-10 were used.…”
Section: Resultsmentioning
confidence: 99%
“…For the expression of r-proteins in mammalian cells, baculovirus vectors have numerous advantages including: (1) the absence of viral replication, (2) the lack of cytotoxicity, (3) the technical simplicity of vector production, and (4) the large DNA insert capacity (up to 38 kb) allowing the delivery of multiple genes from a single vector (Kost et al 2000). Finally, vaccinia virus vectors have been used to produce rproteins such as nerve growth factor (Edwards et al 1988), Factor VIII (Pavirani et al 1987, and human pro-thrombin (Falkner et al 1992). The infectious nature of the virus is a major concern, and it requires containment in a Biosafety Level 2 laboratory.…”
Section: Viral Expression Vectorsmentioning
confidence: 99%